Storage stability study of ciku leather - Taufik,; Mohamad Nordin, Abdul Karim; Che Man, Yaakob (1991)
A stability study was conducted on ciku leather packed in 0.05 and 0.1 mm polypropylene for a duration of 3 months at ambient temperature and 8°C ± 2°C. Physico-chemical, microbiology and organoleptic evaluation were conducted at an interval of the month. Water activity (AW) during storage increased slightly for all conditions. Textural firmness of the leather decreased significantly (P<0.95) while Hunter colour L, a and b values of leather decreased gradually during storage. Total mold count was low with slight increase during storage. Organoleptic evaluation showed that all samples were acceptable to the panelists up to 3 months of storage.